Man: a contrastive analysis between western and Islamic psychologies - Abdul Razak, Mohd Abbas; Ismail, Nik Ahmad Hisham (2014)
In the field of psychology, the research on man, which started in the ancient past, is an on-going study even during this modern and scientific age. It is an undeniable fact that with the passing of time from the primitive to modern, new things have emerged with regard to the study on man and his nature. Being perennial in nature, the old and the new studies conducted on man, try to unearth and bring to light many of man’s potentials, which were not known previously. Although at times many of these studies complement one another in answering the intricate questions on the nature of man, there are also times when they contradict one another in their understanding on man. In view of this reality, this qualitative research is an attempt to provide a contrastive analysis on the concept of man portrayed in the mainstream Western and Islamic psychologies.